Pengaruh Kepemimpinan Motivasi dan Gaji Terhadap Kinerja Pegawai (Studi Pada Pegawai Kantor Kecamatan Batu) - Rusdiana Rusdiana; Pardiman Pardiman; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine: The influence of leadership, motivation, and salary. The influence of leadership on employee performance, 1) The influence of motivation on employee performance, 2) The effect of salary on employee performance, 3)This study uses quantitative methods with descriptive and inferential analysis. The number of samples used was 50 employee respondents at the Batu District Office, Batu City. The data sources used are primary and secondary sources. Data collection used a questionnaire with a Likert scale measurement while the analysis used was an instrument test, normality test, multiple linear regression analysis, hypothesis testing, and the coefficient of determination (R2) with SPSS 16.0 tools. the results of the study show that leadership greatly influences employee performance because good leaders will provide good facilities to employees so that employees have a strong desire to remain as members of the organization in the Batu District Office, Batu City. Keywords: Leadership, Motivation, Salary and Employee Performance